2017
DOI: 10.21511/imfi.14(3).2017.06
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of commercial banks revisited: new evidence from oil and non-oil exporting countries in the MENA region

Abstract: This paper investigates the determinants of commercial bank profitability in oil and non-oil countries of the Middle East and North Africa (MENA) region using data from 11 countries over the period [2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014]. Since banks are under no obligation to fill reports to Bankscope database, irregular reporting banks are omitted from the sample and the model is re-estimated using only regular reporting banks, and a comparative analysis between total banks' sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Pre- and post-crisis researches using the same bases to analyze bank profitability (Athanasoglou et al, 2006 ; Brei et al, 2020 ; Budhathoki et al, 2020 ; López et al, 2020 ; Tercero-Lucas, 2020 ) showed similar results. The global financial crisis has had a favorable impact on bank profitability (Abdullah and Tan, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pre- and post-crisis researches using the same bases to analyze bank profitability (Athanasoglou et al, 2006 ; Brei et al, 2020 ; Budhathoki et al, 2020 ; López et al, 2020 ; Tercero-Lucas, 2020 ) showed similar results. The global financial crisis has had a favorable impact on bank profitability (Abdullah and Tan, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%